/h/‐dropping and occupational role in Stoke‐on‐Trent's pottery industry. (3rd May 2021) - Leach, Hannah
Abstract: This article examines /h/‐dropping in the occupational community of Stoke‐on‐Trent's pottery industry. Using oral history interviews, the article presents quantitative statistical analysis of linguistic and social factors influencing /h/‐variation among these speakers, showing that specific occupational department is the best social predictor of levels of /h/‐dropping. Speakers with more manual, factory‐floor‐based roles show consistently high rates of /h/‐dropping, while speakers with less manual, more varied and/or esteemed roles show lower, and more variable, rates. This suggests a reanalysis of the broad social meanings of /h/ on a local level to enact a hierarchy internal to the industry. Qualitative analysis of individual speakers is employed to explore social meanings of /h/ in this community and how these create and reflect broader social categories. Discussion is linked to wider themes of the role of occupation in social class groupings used in variationist sociolinguistics, suggesting complexity within the classic 'working‐class' category.